Adaptive Super-Twisting Sliding Mode Control for Mobile Robots Based on High-Gain Observers - Haitao Liu; Jianhao Nie; Jian Sun; Xuehong Tian (Journal of Control Science and Engineering)
In this paper, a robust adaptive output feedback control strategy based on a sliding mode super-twisting algorithm is designed for the trajectory tracking control of a wheeled mobile robot. First, a robust adaptive law is designed to eliminate the influence of parameter uncertainties. Second, a double-power sliding mode surface is designed to improve the response speed of the robot system. Finally, a high-gain observer is employed to estimate the speed information. The stability of the closed-loop system is proved using the Lyapunov stability theorem. The effectiveness of the proposed control strategy is verified by simulation.